Anthelmintic prescribing patterns of a sample of general practitioners from selected areas in the Colombo district of Sri Lanka - Gunawardena GSA; Siriwardana C; Paranavitane S; Ismail M; Fernando S (Wolters Kluwer Medknow Publications, 2008)
General Practitioners (GPs) provide first contact care of children and pregnant mothers in the community. This study ascertained the prescribing pattern of anthelmintics to children and pregnant women by a sample of GPs from the district of Colombo. Two hundred medical practitioners engaged in full-time General Practice (100 urban and 100 rural), were selected randomly. A pre-tested interviewer-administered questionnaire was used to collect data. A total of 183 GPs aged between 26 and 72 years (median 38) participated with 94 coming from urban areas. Seventy percent of the GPs were male. Almost 13% of GPs from urban areas had a Postgraduate degree in comparison to 4.5% from the rural areas ( P < 0.05). Over 50% of GPs had 6-20 years of service and over 30% treated 16-30 patients daily. Seventy-three percent of GPs from rural areas accessed health-related reading material either daily or weekly in contrast to only 40% from urban areas ( P < 0.001). All GPs prescribed anthelmintics to children. Pyrantel pamoate was the preferred anthelmintic used for children by both groups. Approximately 55% and 64% of GPs from urban and rural areas, respectively, prescribed anthelmintics during pregnancy. A majority of GPs prescribed drugs after the first trimester. However, 25% from urban areas gave drugs during any trimester ( P < 0.001). Regression analysis revealed that GPs with postgraduate qualifications, those having frequent access to health-related material and those seeing more than 30 patients daily, prescribed anthelmintics to pregnant women more often. Although routine de-worming of pregnant women and children should occur through government antenatal and well-baby clinics, and through the schools de-worming programme, it may not happen due to various reasons. Thus, GPs play a vital role in achieving good coverage of anthelmintics among children and pregnant women. Making available clear national guidelines on prescribing anthelmintics in Sri Lanka would improve the prescribing patterns of anthelmintics among GPs.